Alloying effect on solidification behaviour and grain refinement in Ti45Al2Nb2Ta0.8B and Ti45Al2Nb2Hf0.8B. (December 2020) - Li, Jing; Jeffs, Spencer; Whittaker, Mark; Martin, Nigel
Abstract: The solidification process of Ti45Al2Nb2Ta0.8B (B4522Ta) and Ti45Al2Nb2Hf0.8B (B4522Hf) Bridgman samples were studied through directional solidification. Boron addition at 0.8 at. % was found to have changed the orientation relationship of peritectic α with β dendrites. The peritectic alpha is randomly oriented in both B4522Ta and B4522Hf, it was likely to be inoculated by boride precipitates at the β/liquid interfaces during peritectic transformation. The alloying effect of Ta and Hf on the peritectic reaction was similar. Borides precipitated earlier in Ta-containing alloy than that in Hf-containing alloy during solidification. Highlights: Borides precipitated earlier in Ta-containing alloy than that in Hf-containing alloy during solidification. The peritectic α is likely to be inoculated by boride precipitates at the β/liquid interfaces. The alloying effect of Ta and Hf on the peritectic reaction was similar.